A Case Study On Drug Induced Hepatomegaly associated With Dengue Infection - SATHISHA .T.G,; PAVITHRA. V,; KASTURI K,; SAMBASIVA RAO KRS,; MANJUNATHA GOUD B.K,; BHAVNA NAYAL, (International Journal of Pharma and Bio Sciences, 2011)
Dengue is a viral fever characterized by rashes and renal complication. Nimesulide is an analgesic and antipyretic drug. This case is an unusual combination of dengue and drug induced damage of liver in a 6 month old female baby with a history of flu like symptoms with chills, rigors and drowsiness. She was administered a syrup of two drugs namely nimesulide and paracetamol. Serology of dengue confirmed primary infection. All the symptoms and signs returned to normal after termination of the nimesulide and supportive treatment. This case differs from the other cases based on the time of onset and indicates that nimesulide may induce hepatomegaly in the first few days of administration. Hence, patients receiving nimesulide should be regularly monitored with serial serum transaminases beginning from the first week of intake or the prescription of nimesulide should be banned all over the world.